Optimal planning of phase II/III programs for clinical trials with multiple endpoints - Kieser, Meinhard; Kirchner, Marietta; Dölger, Eva; Götte, Heiko (Pharmaceutical statistics, 2018)
Owing to increased costs and competition pressure, drug development becomes more and more challenging. Therefore, there is a strong need for improving efficiency of clinical research by developing and applying methods for quantitative decision making. In this context, the integrated planning for phase II/III programs plays an important role as numerous quantities can be varied that are crucial for cost, benefit, and program success. Recently, a utility-based framework has been proposed for an optimal planning of phase II/III programs that puts the choice of decision boundaries and phase II sample sizes on a quantitative basis. However, this method is restricted to studies with a single time-to-event endpoint. We generalize this procedure to the setting of clinical trials with multiple endpoints and (asymptotically) normally distributed test statistics. Optimal phase II sample sizes and go/no-go decision rules are provided for both the “all-or-none” and “at-least-one” win criteria. Application of the proposed method is illustrated by drug development programs in the fields of Alzheimer disease and oncology.